Conservation of transnational species: The tensions between legal requirements and best scientific evidence. Issue 11 (7th September 2021) - Pinn, Eunice H.; Macleod, Kelly; Tasker, Mark L.
Abstract: This paper describes the tensions between the legal requirements for conservation and the most beneficial biological practice for mobile transnational marine species, using the harbour porpoise ( Phocoena phocoena ) in European Atlantic waters as a case study. Harbour porpoise are the smallest and one of the most abundant cetaceans occurring throughout the European continental shelf waters, and are affected by human activities occurring in the same waters, especially certain fishing activities. The Convention on the Conservation of European Wildlife and Natural Habitats (the Bern Convention) and its implementing legislation the Council Directive on the Conservation of Natural Habitats and of Wild Fauna and Flora 92/43/EEC (i.e. the Habitats Directive) are the main legal drivers for species conservation throughout the European Union. They aim for the long‐term achievement of favourable conservation status and make provision for the use of two conservation measures: protected areas and strict protection measures. The strict protection measures aim to ensure that all forms of deliberate killing are prevented, and that where incidental killing and capture occurs, it does not have a negative effect on conservation status. The conservation of harbour porpoise is currently dependent upon tackling the key issue of bycatch in fisheries. However, in challenges to Member States on their application of the Habitats Directive, the European Commission has chosen to focus on site designation rather than the implementation of the strict protection measures required to monitor and, where necessary, reduce bycatch. This tension between a legal focus on the designation of protected areas instead of tackling threats such as bycatch has potentially led to negative conservation consequences for harbour porpoise and, in part, may explain why wider marine biodiversity has continued to deteriorate in Europe.